Perioperative Anesthetic Management of Brain Abscess Evacuation in a Child with Double Outlet Right Ventricle: A Case Report - Rio Kharisma Putra; Buyung Hartiyo Laksono; Eko Nofiyanto; Fanniyah; Ruddi Hartono (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Double outlet right ventricle (DORV) is a rare congenital heart defect where both the aorta and pulmonary artery arise from the right ventricle. This anomaly poses unique challenges for anesthetic management, especially during intracranial surgeries. Case presentation: We present the case of a 7-year-old female child diagnosed with a brain abscess and DORV, who underwent open evacuation and cranioplasty. Anesthetic management focuses on maintaining hemodynamic stability and ensuring adequate oxygenation. The patient was successfully extubated postoperatively and transferred to the intensive care unit (ICU) for close monitoring. Conclusion: Surgical interventions in patients with DORV require careful preoperative evaluation and close perioperative monitoring to minimize morbidity and mortality. This case highlights the importance of a multidisciplinary approach and meticulous anesthetic management in ensuring a successful outcome.